AN ANALYSIS OF CLASSROOM CHARACTER EDUCATION IN ENGLISH LESSONS BASED ON THE 2013 CURRICULUM - Ratih, I. A. M.; Marhaeni, A. A. I. N.; Hadisaputra, I. N. P. (Jurnal Pendidikan Bahasa Inggris undiksha, 2019)
The study attempted to analyze the implementation of character education in the English lessons at SMP Negeri 1 Banjar. The subjects of the research were the eighth grade students and the English teacher. The researcher analyzed the lesson plans and the implementation to investigate how character education was inserted in the teaching of the four basic skills in English which has been integrated in the process of teaching and learning in 2013 curriculum. The instruments in this study consisted of interview guide, recorder, lesson plan analysis checklist, and observation checklist. Result of the analysis indicates that the teacher inserts the character values in indicators, learning materials, learning steps, and assessment instrument in lesson plans. In teaching and learning activities, character values are also implemented. However, the character values which are inserted in learning activities are different from one with another. It depends on the topic and indicators that will be achieved. In the evaluation, the strategies which were used by the teacher were in the form of advice and scoring rubric to assess character education in the process of teaching and learning.  Keywords: Character education, English lessons